Japan's Foreign Policy Maturation : a Quest for Normalcy. - Cooney, Kevin (East Asia: History, Politics, Sociology and Culture., 2013)
The sudden end of the Cold War took the Japanese foreign policy community by surprise. The Yoshida Doctrine which served Japanese foreign policy so well during the Cold War is no longer a viable foreign policy option. This dissertation examines the restructuring of Japanese foreign policy since the end of the Cold War. Through a series of 56 interviews with Japanese foregin policy elites, the changes in Japanese foreign policy are put into the context of the foreign policy literature.